Development and testing of zinc sulfate and zinc oxide nanoparticle-coated urea fertilizer to improve N and Zn use efficiency - Beig, Bilal; Niazi, Muhammad Bilal Khan; Jahan, Zaib; Haider, Ghulam; Zia, Munir; Shah, Ghulam Abbas; Iqbal, Zahid; Hayat, Asim (Frontiers in Plant Science, 2023)
Nitrogen (N) losses from conventional fertilizers in agricultural systems are very high which might lead towards serious environmental pollution with economical loss. In this perspective, innovative slow release fertilizers were prepared using Zinc (Zn) (nano or bulk) with molasses as environment friendly coatings. Several treatments were prepared with Zn in different (0.25, 0.5 and 4 elemental Zn) % using molasses as a binder. The samples were tested for urea N release rate, water-soil leaching and crushing strength to assess coating impact on final finished product. Pot experimentation was also done simultaneously to check agronomic effects of Zn coated slow release urea on wheat crop growth. The ZnO-NPs were prepared from ZnSO4.7H2O and characterized using SEM, XRD and FTIR. The laboratory and pot results confirmed that the ZnO-NPs treatments boost wheat growth yield due to reduced N and Zn release. The UZnNPs2 (0.5% ZnO-NPs) demonstrated the best results among all the treatments in terms of slow nutrient release, N and Zn uptake and grain yield. The UZnNPs2 increased plant yield by 34% (4515 vs 3345 kg ha-1) relative to the uncoated prill treated crop due to slower release of Zn and N.